Effect of Different Cross-Infection Control Barriers on Intensity of Curing Light: An In-Vitro Study - Saqib Naeem Siddique, Palwasha Babar, Huma Tanvir, Hafsa Aslam, Hamda Khurram, Eesha Hassan (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To evaluate the effect of different cross infection control barriers on the intensity of the curing light. Study Design: In-vitro experimental study. Place and duration: Department of Operative and Pediatric Dentistry, The University of Lahore from January to March 2022. Methodology: The intensity of the light-curing unit was measured using a radiometer. The intensity of light without using any barrier was taken as control. Four barriers were used; polythene glove, latex glove, cling film wrap and standard barrier tape. Ten measurements for each group were performed after placing each type of protection barrier and the average was taken. The data was analyzed using SPSS v 22. Results: The mean value for light intensity without using any barrier was found to be 737.6 mW/cm2. The light intensity was maximum for cling film, polythene glove, barrier tape and latex glove with mean values of 720.6 mW/cm2, 581.2 mW/cm2, 541.7 mW/cm2 and 255.06 mW/cm2 respectively. A comparison of the output values without barrier and with different barriers showed a statistically significant difference with all barriers except cling film. Conclusion: It was found that cling film, polythene glove and barrier tape could serve as a barrier to cover the tip of the light curing unit. Keywords: Dental curing light, cross-infection, composite resin